The Flow Separation of Peristaltic Transport for Maxwell Fluid between Two Coaxial Tubes - S. Z. A. Husseny; Y. Abd elmaboud; Kh. S. Mekheimer (Abstract and Applied Analysis)
We study the peristaltic mechanism of an incompressible non-Newtonian biofluid (namely, Maxwell model) in the annular region between two coaxial tubes. The inner tube represents the endoscope tube. The system of the governing nonlinear PDE is solved by using the perturbation method to the first order in dimensionless wavenumber. The modified Newton-Raphson method is used to predict the flow separation points along the peristaltic wall and the endoscope tube. The results show that the presence of the endoscope (catheter) tube in the artery increases the pressure gradient and shear stress. Such a result seems too reasonable from the physical and medical point of view.